GIST a rare abdominal tumor and our surgical experience - Saroj, Sanjay Kumar; Kumar, Akhilesh; Prasad, Rina; Pratap, Arvind; C. J., Vidyasagar; Verma, Saurabh Kumar; Bhartiya, Satyanam Kumar; Shukla, Vijay Kumar (International Journal of Research in Medical Sciences, 2022)
Background: GISTs are rare abdominal tumors, encountered as the most common mesenchymal neoplasms of the gastrointestinal (GI) tract leading to GI bleeding. We report a changing trend of diagnosis and management in Indian patients. Methods: The retrospective data was collected from medical records and 62 cases of GIST from 2003 to 2020 in General surgical unit of BHU. They were divided in three groups. In group A (36) patients only surgery, group B (14) patients surgery than adjuvant chemotherapy and in group C (12) who received neoadjuvant chemotherapy then surgery. Preoperatively, USG and CT scans of the abdomen were the main investigations, others being upper gastrointestinal endoscopy and chest x-ray confirm by histopathological and immunohistochemical evaluation. Results: The mean age at presentation was 42.8 years (range 17-74 years) and mean duration of symptoms was of 5 months (range 10 days-2 years). It was from the stomach, (06) duodenum (14) jejunum, (06) ileum, (1) caecum and (4) from the mesentery and (4) from retroperitoneum. 44 cases had low grade benign tumors and 18 malignancies. In group A, 22 (61%) patients showed recurrence in group B, 06, (42%) patients showed recurrence and group C, 02 (33%) patient showed recurrence. Conclusions: Most of the tumours were benign and surgical resection is the mainstay of treatment. However, the patients in which only surgery was done showed maximum recurrence and patients who received neoadjuvant chemotherapy then surgery followed adjuvant chemotherapy showed minimum recurrence.